Capsule Endoscopy in Patients with Implantable Electromedical Devices is Safe. (3rd April 2013) - Harris, Lucinda A.; Hansel, Stephanie L.; Rajan, Elizabeth; Srivathsan, Komandoor; Rea, Robert; Crowell, Michael D.; Fleischer, David E.; Pasha, Shabana F.; Gurudu, Suryakanth R.; Heigh, Russell I.; Shiff, Arthur D.; Post, Janice K.; et al.
Abstract : Background and Study Aims . The presence of an implantable electromechanical cardiac device (IED) has long been considered a relative contraindication to the performance of video capsule endoscopy (CE). The primary aim of this study was to evaluate the safety of CE in patients with IEDs. A secondary purpose was to determine whether IEDs have any impact on images captured by CE. Patients and Methods. A retrospective chart review of all patients who had a capsule endoscopy at Mayo Clinic in Scottsdale, AZ, USA, or Rochester, MN, USA, (January 2002 to June 2010) was performed to identify CE studies done on patients with IEDs. One hundred and eighteen capsule studies performed in 108 patients with IEDs were identified and reviewed for demographic data, method of preparation, and study data. Results. The most common indications for CE were obscure gastrointestinal bleeding (77%), anemia (14%), abdominal pain (5%), celiac disease (2%), diarrhea (1%), and Crohn's disease (1%). Postprocedure assessments did not reveal any detectable alteration on the function of the IED. One patient with an ICD had a 25-minute loss of capsule imaging due to recorder defect. Two patients with LVADs had interference with capsule image acquisition. Conclusions. CE did not interfere with IED function, including PM, ICD, and/or LVAD and thus appears safe. Additionally, PM and ICD do not appear to interfere with image acquisition but LVAD may interfere with capsule images and require that capsule leads be positioned as far away as possible from the IED to assure reliable image acquisition.